RANCANG BANGUN DASHBOARD BUSINESS INTELLIGENCE UNTUK VISUALISASI DATA PASIEN (STUDI KASUS: PUSKESMAS PAKAN KAMIS) - Nazifa Hayati; Dini Nurmalasari (Politeknik Caltex Riau, 2021)
The Public Health Center (Puskesmas) is a technical implementation unit of the district / city office which is responsible for carrying out health development in a work area. One of the existing community health centers is the Pakan Kamis puskesmas. Based on the interviews conducted, the puskesmas still experienced difficulties in seeing the pattern of disease spread, drug use patterns and patient development, because the process of recapping and calculating data was still done manually. This causes the puskesmas management to have difficulty in analyzing data and obtaining information for decision making. Therefore, a web-based business intelligence dashboard was created that can visualize patient data related to these problems. This Business Intelligence dashboard is built using the PHP programming language and MySQL database. From the results of user satisfaction testing, it was found that 97% of the business intelligence system dashboard for visualizing patient data was in accordance with the needs and could assist the health center in monitoring the pattern of disease spread, patient usage and development, as well as assisting the health center in analyzing data to make appropriate decisions. and efficient. Keywords: Puskesmas Pakan Kamis, Patient Data, Visualization, Dashboard, Business Intelligence